The Determinants of Entrepreneurial Intention among Generation Z during Covid-19 Pandemic: Evidence from Indonesia - Dety Nurfadilah; Lintang Tiara; Raynaldo Kharismananda (ADI Publisher, 2020)
Generation Z, known as people who grow with technology, have a preference for starting their own business which is estimated to be different than other generations during the covid-19 pandemic. Understanding their behavior becomes very important because they will become the next generation that drives the economic sector. This study aimed to investigate the key determinants of entrepreneurial intention among generation Z during the Covid-19 pandemic. 225 data were collected through online tools and analyzed using partial least square – structural equation modeling. The finding indicates that entrepreneurial intention among generation Z is positively correlated and influenced by family’s entrepreneurial tradition, profit orientation, and personality traits. This study used the family's entrepreneurial tradition and profit orientation as new variables which have received little attention to determine the entrepreneurial intention. The phenomenon of covid-19aa will bring new contributions to the field of management and entrepreneurship.